The Implementation of Tarbiyyah Program based on the Hostel Student Development Module (MPMA): A Study at the Religious Secondary Schools (SMKA) in Penang - Mohd Suhardi, Mat Jusoh; Shaik Abdullah, Hassan Mydin; Jasni, Sulong (Human Resource Management Academic Research Society (HRMARS), 2018)
Tarbiyyah or education is an utmost tool to nurture our youth’s personality nowadays amidst of global threats and challenges in the non-boundary world today. Thus, this research discusses the implementation of tarbiyyah programme in order to develop student’s personality at the hostels of religious secondary schools in Penang based on the Hostel Student Development Module (MPMA) issued by the Ministry of Education Malaysia. The main objective of this study is to examine the implementation of tarbiyyah programme based on the elements of rūhiyyah (spiritual) and 'aqliyyah (intellectual) for student’s personality development in religious secondary schools, as well as to evaluate the effectiveness of programme implementation in the aspects of shaping student’s personality. Finally, to propose some improvements as a personality development module in the term of spiritual and intellectual achievement. This research employs qualitative methods whereby data was collected through observations and interviews. In general, the findings of qualitative research showed that the implementation of tarbiyyah programme can improve student self-esteem, especially in the aspects of spiritual and intellectual intelligence. Thus, this study concludes that the implementation of tarbiyyah programme based on the Hostel Student Development Module (MPMA) is very relevant and appropriate to be implemented at educational institutions as a personality development module.